ANORGANIK KIMYODA «ISHQORIY METALLAR » MAVZUSINI O`QITISHNING PEDAGOGIK VA INFORMATSION TEXNOLOGIYA ASOSIDA DARS ALGORITMI - Ajieva, M.B.; Bekimbetova, G.N.; Sultonov, D.Q.; Umrbekova, M.U. (SCIENCE and SOCIETY, 2023)
This article briefly described didactic tools and recommendations for improving the effectiveness of lessons on teaching the topics of the Alkali Metals section, and also presented the results of introducing new pedagogical technologies based on pedagogical experiments into the lesson. A pedagogical experiment on the topic was conducted and tested in schools in the Shomanai and Ellikkala districts. Inorganic chemistry is taught in schools, and 22 hours are allotted for the topic "Alkali metals" in the curriculum. To create a methodology for teaching the subject, an algorithm was developed for using didactic tools and tools, taking into account the characteristics of each lesson.